Effects of brief acceptance and commitment therapy (ACT) on subjective cognitive impairment in breast cancer patients undergoing chemotherapy. Issue 6 (2nd November 2021) - Shari, Nurul Izzah; Zainal, Nor Zuraida; Ng, Chong Guan
Abstract: Purpose: This study examined the efficacy of a brief acceptance and commitment therapy (ACT) on subjective cognitive impairment in breast cancer patients undergoing chemotherapy. Methods: Data collection was carried out in 3-time points: baseline (T1), screening (T2), and post-treatment (T3). Respondents who had significant subjective cognitive impairment were randomly divided into two groups: intervention (n = 30) and waitlist (n = 30). Respondents in the intervention group received 4 sessions of 1 hour of ACT therapy. Findings: Respondents in the intervention group showed significant improvement in subjective cognitive impairment, depression, anxiety, and psychological inflexibility after the ACT intervention ( p  < 0.05). After controlling the covariates, group differences in all variables were significant except for fatigue and psychological inflexibility has the highest effect size ( d  = 4.69). Conclusion: ACT could be considered as an effective intervention to ameliorate subjective cognitive impairment, anxiety, depression, and psychological inflexibility in breast cancer patients undergoing chemotherapy. Implications for Psychosocial Providers: This study highlights the importance of screening for subjective cognitive impairment in breast cancer patients undergoing chemotherapy and heightens their opportunity to receive proper management as earlier as possible.